2018
DOI: 10.1016/j.ehj.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of P wave dispersion and interatrial block in patients with systolic heart failure and their relationship with functional status, hospitalization and one year mortality

Abstract: Background and objectivesP-wave dispersion (PWD) and Interatrial block (IAB) are common in heart failure (HF), and could be associated with adverse cardiac events. We aimed to assess the prevalence of PWD and IAB and their relationship with functional status, hospitalization and mortality rate in patients with systolic HF.MethodsWe enrolled 110 HF patients in sinus rhythm & LVEF <50%. Patients had undergone clinical evaluation, 6 min walking test (6MWT), 12-lead electrocardiography (ECG), 24-h Holter ECG & ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Moreover, prolongations in amplified PWDs were predictive of new‐onset AF in patients with HF with preserved ejection fraction 33 . Similar findings have been observed in the context of HF with reduced ejection fraction 34 . These findings are in keeping with prolonged total atrial conduction time, which reflects atrial remodelling, with poorer cardiac prognosis in HF 35 …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, prolongations in amplified PWDs were predictive of new‐onset AF in patients with HF with preserved ejection fraction 33 . Similar findings have been observed in the context of HF with reduced ejection fraction 34 . These findings are in keeping with prolonged total atrial conduction time, which reflects atrial remodelling, with poorer cardiac prognosis in HF 35 …”
Section: Discussionsupporting
confidence: 67%
“…33 Similar findings have been observed in the context of HF with reduced ejection fraction. 34 These findings are in keeping with prolonged total atrial conduction time, which reflects atrial remodelling, with poorer cardiac prognosis in HF. 35 Recent studies have explored the use of automated ECG indices for risk prediction in different cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 55%
“…IAB is also a frequent accompanying abnormality in patients with heart failure. Abdellah et al (12) evaluated the frequency and clinical associates of IAB in patients with systolic heart failure. They found that patients with IAB had significantly higher functional classes and increased mortality during 12-month follow up period.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of this study is yet to be determined. In the last few years, increasing evidence about the impact of IAB on clinical outcomes, including hospital admissions, poor functional capacity, and mortality has been published [26]; however, until now, there are no recommendations for the follow-up or treatment of these patients so it remains to be seen how identifying patients with IAB could benefit their health. In the case of PLWH (who are considered at higher cardiovascular risk than uninfected people), the global rapid increase in mortality due to cardiovascular events requires a more proactive approach in implementing prevention strategies that could aim for lessening the burden of disease.…”
Section: Discussionmentioning
confidence: 99%